COMPARATIVE ANALYSIS OF WASTE REDUCTION METHODS FOR SUSTAINABLE MANUFACTURING SYSTEMS USING CONCURRENT TRIANGULATION MODEL. (Nigerian Journal of Technology, 2020)
The aim of this study is to carry out a comparative analysis of waste reduction methods for sustainable manufacturing systems using Cronbach alpha and concurrent triangulation model. The objective of this research is to establish an ideal sustainable manufacturing waste disposal method. Reliability test results showed that the Cronbach alpha values used to measure the internal consistency of responses recorded  for recycling, reuse, reduce, remanufacture and landfilling were  0.8160 , 0.8100 , 0.7760 , 0.7550  and 0.7340 respectively  with recycling recording the highest internal consistency. The concurrent triangulation model recorded results showed that recycling recorded a total of 184 respondents at the highest percentage of 51.11 %, reuse recorded a total of 58 respondents with 16.13 %, remanufacture recorded 43 respondents at 11.94%, reduce recorded a total of 38 respondents at 10.55 %, and Landfilling had 37 respondents with 10.27 %. Hence Recycling was selected as the most appropriate method. http://dx.doi.org/10.4314/njt.v39i3.13